Atlas of Fallen Dust in Kuwait - Al-Dousari, Ali (Springer International Publishing : Imprint: Springer, 2021)
This open access book serves as an atlas of deposited dust and dust storms in Kuwait in relation to local and global regions. It features a wealth of maps and images of dust storm trajectories in the region, together with detailed descriptions of the chemical and physical properties of fallen dust, including the amount, particle size, statistical parameters, spectra absorption, dust mineralogy, trace and major elements, organic matter, associated pollen, and radionuclides and connected pollutants. Given its scope, the book is a valuable resource for a broad range of researchers, including geologists, chemists, environmentalists, botanists, air quality specialists, nanotechnology scientists, and solar energy experts.